Assessment of the Potential Epidemic Hazard as Regards International Public Events in Terms of the Currently Important Infectious Diseases - S. K. Udovichenko; A. V. Toporkov; I. G. Karnaukhov; E. V. Kuklev; O. V. Kedrova; V. A. Safronov; A. S. Razdorsky; N. V. Popov; T. V. Knyazeva; V. P. Toporkov; V. V. Kutyrev (Проблемы особо опасных инфекций, 2013)
International public events (IPE) present some actual epidemiological problems requiring proper methodological elaboration. In this respect for the first time developed has been the scheme of assessment of their potential epidemic hazard (PEH), based on integrated evaluation of epidemiological risk as regards infectious diseases listed in the IHR (2005). On the cholera model demonstrated is the fact that high priority hazard of public events emerges when those are combined with such elements of epidemiological risk as territory and time of a threat, as well as risk factors and risk contingents. Thus the integral effect of all elements realization is manifested through high probability of infectious disease importation, which is associated with emergency situation, into the public event location and the disturbance of mass gathering progress. Reliability and functionality of the developed scheme is verified on other infections too. PEH assessment procedure allows for timely identification of priority goals, for rating means and capacities, organizational resources, methodological and technological arrays for the provision of sanitary-epidemiological welfare and biological safety when managing public event.